Preparation and quality analysis of walnut and purple rice yogurt - MU Hongyu, LI Cailan, WU Bo, CHEN Rong, SHENG Jun, ZHAO Cunchao, YU Zhijin (Zhongguo niangzao, 2024)
In order to develop a plant-based walnut and purple rice yogurt, the effects of walnut kernel addition, purple rice addition, carboxymethyl cellulose (CMC) addition and fermentation time on the quality of the yogurt were investigated through single factor tests using sensory scores and acidity as evaluation indexes. The optimal conditions for the production of walnut and purple rice yogurt were determined through response surface tests, and the quality of the finished yogurt was comprehensively analyzed and compared with that of unfermented purple rice milk. The results showed that the optimal process conditions for walnut and purple rice yogurt were obtained by single factor and response surface tests as follows: walnut kernel addition 12.5%, purple rice addition 12%, CMC addition 0.3%, and fermentation time 14 h. The yogurt obtained under the process had rich flavor, uniform color, delicate taste, with a sensory score of 86.87 and acidity of 49.05 °T. Compared with unfermented walnut and purple rice milk, the percentage of monounsaturated fatty acids in walnut and purple rice yogurt increased by 33.03%, the sweet amino acids increased by 25.76%, and the bitter amino acids decreased by 20.23%. The results of principal component analysis (PCA) showed that there were significant differences between walnut milk with purple rice and walnut and purple rice yogurt, which could be distinguished by principal component analysis. The monounsaturated fatty acids and sweet amino acids were positively correlated with the comprehensive quality of walnut and purple rice yogurt, which made the walnut purple rice yogurt obtained by fermentation more nutritious and more palatable.